Waste Analysis in the Packaging Process Using a Lean Manufacturing Approach for Improving Production Performance - Rekha Rofiq Tya Azzahra; Wiwin Widiasih (Fakultas Teknik Universitas 17 Agustus 1945 Surabaya, 2026)
This study aims to identify and reduce waste in the Aluvo product packaging process at PT XYZ using Value Stream Mapping (VSM) and Waste Assessment Model (WAM). Data were collected through direct observation and internal company documents over the period September 2025 to February 2026. Waste identification was carried out using a Waste Assessment Questionnaire (WAQ) distributed to five respondents directly involved in the packaging line, and further prioritized through Waste Relation Matrix (WRM) analysis. The results indicate that the dominant wastes are defect (WMV = 4.701) and overprocessing (WMV = 4.650). The current state Process Cycle Efficiency (PCE) was 54.1% with a total lead time of 170 seconds. Following the implementation of improvement proposals including preventive maintenance scheduling, standard operating procedure (SOP) revision, operator training, and layout improvement the future state PCE increased to 83.3% with lead time reduced to 84 seconds. Key Performance Indicators also improved: average defect rate decreased from 12.7% to 10.2%, machine availability increased from 87.11% to 90.33%, and productivity increased from 3,611 pcs/hr to 3,972 pcs/hr.